KECAKAPAN PERSEPSI DALAM PEMBELAJARAN KETERAMPILAN PSIKOMOTORIK KESEGARAN JASMANI DAN SENI GERAK (Harmonia: Journal of Arts Research and Education, 2009)
Learning movement /psychomotor skill in art of movement and body health, both complexand simple one, need such good integration of students’ physical and physic function. To getthe maximum result, it needs perseverance, correctness, integrity, concentration andcoordination between perception and movement. In fact, students have perceptual and physicability. Efficiency in perceptual ability closely related to students’ development in cognitive,affectiv